Stability and kinetics of folding of the domain-swapped dimer of the FOXP3 forkhead domain - Perumal, Kershia (My University, 2018)
Crystal structures show that the forkhead domain (FHD) of FOX transcription factors is monomeric, except in the P-subfamily which exhibit formation of domainswapped dimers. The crystal structure of the FOXP2 FHD shows a mixture of monomer and domain-swapped dimer (DSD) whereas the FOXP3 FHD is solely dimeric. The FOXP3 DSD is shown to be crucial for its suppressive function. Furthermore, mutations in the FOXP3 FHD are linked to a severe autoimmune disease known as the IPEX (immunodysregulation, polyendocrinopathy, enteropathy, X-linked) syndrome. Here, we explore the domain-swapping mechanism of the FOXP3 DSD using urea-induced equilibrium unfolding, stoppedflow kinetics, size-exclusion chromatography, circular dichroism, intrinsic and extrinsic (ANS) fluorescence spectroscopy. Our results show that the FOXP3 DSD is completely dimeric at micromolar concentrations as low as 4 µM which is in contrast to classical domain-swapped structures which exhibit a mixture of monomer and dimer. Interestingly, equilibrium unfolding of the FOXP3 FHD monitored by tryptophan fluorescence follows a three-state (N2↔I2↔2U) folding mechanism whereby the dimer partially unfolds to form a dimeric intermediate which precedes complete unfolding. Urea-induced equilibrium unfolding monitored by circular dichroism shows a two-state folding mechanism with a free energy change of unfolding of 19.3 ± 0.97 kcal.mol-1. Circular dichroism spectra shows that the intermediate strongly resembles the native state, whereas intrinsic and ANS fluorescence spectra as well as size-exclusion chromatography reveal that the structure of the intermediate is not as compact as the native state. Stoppedflow kinetics were monitored using tryptophan fluorescence above 320 nm. Unfolding kinetics indicate one kinetic phase except for the single jump from native to the intermediate state. Refolding kinetics are biphasic. A three-state unfolding mechanism ((N2↔I2↔2U) is proposed for the folding pathway of the FOXP3 DSD with the primary hydrophobic interface being disrupted upon formation less compact molten-globule intermediate which then dissociates into monomers (burst phase in I ↔ U transition) and subsequently unfolds completely.